Association of Antibiotics Administration Timing With Mortality in Children With Sepsis in a Tertiary Care Hospital of a Developing Country - Alsadoon, Alaa; Alhamwah, Moudi; Alomar, Bassam; Alsubaiel, Sara; Almutairi, Adel F.; Vishwakarma, Ramesh K.; Alharthy, Nesrin; Kazzaz, Yasser M. (Frontiers in Pediatrics, 2020)
Objective: To investigate the association between antibiotics administration timing with morbidity and mortality in children with severe sepsis and septic shock, presenting to a tertiary care center in a developing country. Methods: This is a retrospective study of children aged 14 years or younger diagnosed with severe sepsis or septic shock at a free-standing tertiary children’s hospital in Saudi Arabia between April 2015 and February 2018. We investigated the association between antibiotic administration timing and pediatric intensive care unit (PICU) mortality, PICU length of stay (LOS), hospital LOS, and ventilation-free days after adjusting for confounders. Results: Among the 189 admissions, 77 patients were admitted with septic shock and 112 with severe sepsis. Overall, the mortality rate was 16.9%. The overall median time from sepsis recognition to antibiotic administration was 105 minutes (IQR: 65–185.5 min); for septic shock patients, it was 85 minutes (IQR: 55–148 min), and for severe sepsis, 130 minutes (IQR: 75.5–199 min). Delayed antibiotic administration (> 3 hours) was associated with 3.85 times higher PICU mortality (95% confidence intervals 1.032 to 14.374) in children with septic shock than in children who receive antibiotics within 3 hours, after controlling for severity of illness, age, comorbidities, and volume resuscitation. However, delayed antibiotics administration was not significantly associated with higher PICU mortality in children diagnosed with severe sepsis. Conclusions: Delayed antibiotics administration in children with septic shock admitted to a free-standing children’s hospital in a developing country was associated with PICU mortality.